Fourier analysis on finite groups with applications in signal processing and system design - Stankovic Radomir S; Astola Jaakko T; Moraga Claudio (New Jersey John Wiley, 2005)
The book examines aspects of Fourier analysis on finite non-Abelian groups and discusses different methods used to determine compact representations for discrete functions providing for their efficient realizations and related applications. Switching fun
Keywords: Fourier analysis; Signal processing; System design